The association between follicular size at time of spontaneous rupture and pregnancy rates in clomiphene citrate treated PCOS patients in coit cycles - Portocarrero, Carlos Sanchez [UNESP]; Gomes Sobrinho, David; Nakagawa, Hotomi; Silva, Adelino; Carvalho, Bruno; Sarkis, Nathália; Peraçoli, José Carlos [UNESP]; Cardoso, Maria Teresinha (Taylor & Francis, 2015)
Objective: To investigate the follicular size at spontaneous rupture on pregnancy rate in patientswith polycystic ovary syndrome (PCOS) undergoing clomiphene citrate (CC) ovulation.Design: Cross-sectional study.Patients and methods: One hundred and four women with ovulatory cycles after use of CCfollowed by ultrasound to determine the follicle size at the time of rupture, which wassubsequently correlated with the occurrence of pregnancy or not in coit cycles.Results: In the group of follicular rupture at a mean diameter25 mm (n¼54), pregnancy ratewas 35.1% and when follicular rupture occurred at a mean diameter425 mm (n¼50), it was34% (p40.05). When different diameters at follicular rupture were randomly correlated with thepregnancy rate, there was no significant difference.Conclusion: Our data suggest that the occurrence of pregnancy after ovulation induction withCC in women with PCOS is not associated with follicle size at the time of rupture.
Keywords: Anovulatory infertility; Clomiphene citrate; Follicular size; PCOS; Pregnancy rate